2011
DOI: 10.1002/nau.21151
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle and transversus abdominis activation in abdominal hypopressive technique through surface electromyography

Abstract: Based on our results, the AHT is less effective than PFM contraction alone, and adding PFM contraction to AHT also improves the TrA contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 18 publications
4
58
0
8
Order By: Relevance
“…In addition to digital vaginal palpation, surface electromyography (SEMG) could complement PF assessment during pregnancy. SEMG has shown good validity and interobserver reproducibility during evaluations of the electrical activity of PFM [1,[9][10][11]. Although SEMG records the electrical activity produced by the recruitment of motor units and not muscle strength itself, some studies indicate that there is good correlation between the number of activated motor units and muscle strength [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to digital vaginal palpation, surface electromyography (SEMG) could complement PF assessment during pregnancy. SEMG has shown good validity and interobserver reproducibility during evaluations of the electrical activity of PFM [1,[9][10][11]. Although SEMG records the electrical activity produced by the recruitment of motor units and not muscle strength itself, some studies indicate that there is good correlation between the number of activated motor units and muscle strength [1].…”
Section: Introductionmentioning
confidence: 99%
“…El estudio mostró una reducción significativa del perímetro de la cintura de 3,5 cm de media y, en un 80% de los casos, una disminución significativa de los síntomas de la incontinencia urinaria con respecto al grupo de mujeres que no realizaron la el grupo que utilizó exclusivamente Gimnasia Abdominal Hipopresiva una activación de la musculatura del suelo pélvico en comparación con el tono de reposo (P<0,001). Demostró que la Gimnasia Hipopresiva puede ser una técnica a contemplar en la reeducación de los músculos del suelo pélvico 22 .…”
Section: Recienunclassified
“…Recent studies [1][2][3] have shown that exercise, centered on the abdominopelvic enclosure, could favor the PFM functions.…”
Section: Introductionmentioning
confidence: 99%